Ferroptosis: A Key Driver in Atherosclerosis Progression and Arterial Disease - Amr Elkammash; Abrar Zaki; Omar Tawfik; Sherif Gouda (Reviews in Cardiovascular Medicine, 2024)
Atherosclerosis (AS) is a growing global health epidemic and is the leading cause of cardiovascular health problems, including ischemic stroke, coronary artery disease, and peripheral vascular disease. Despite extensive research on the underlying mechanisms of AS, iron remains an under-investigated mediator in the atherosclerotic process. Iron’s involvement in AS is primarily linked to the iron-induced programmed cell death process known as ferroptosis. Ferroptosis is initiated in endothelial cells when iron overload triggers the Fenton reaction, resulting in the production of reactive oxygen species (ROS) and lipid peroxides. This oxidative stress damages cellular components, ultimately leading to cell death. The review examines the role of iron overload and ferroptosis in the progression and instability of atherosclerotic plaques. Additionally, we explore the potential therapeutic roles of iron chelators and ROS scavengers in mitigating the adverse effects of ferroptosis. The findings indicate that ferroptosis contributes significantly to the progression and instability of atherosclerotic plaques by promoting oxidative damage and cellular dysfunction. Iron chelators and ROS scavengers have shown promise in reducing ferroptosis-induced damage in endothelial cells. These therapeutic agents can potentially stabilize atherosclerotic plaques and prevent the progression of AS. Ferroptosis is a critical yet under-explored pathway in the development and progression of atherosclerosis. Targeting iron-induced oxidative stress through iron chelation and ROS scavenging presents a promising therapeutic strategy for mitigating the adverse effects of ferroptosis on atherosclerotic plaque stability. Further research is needed to validate these therapeutic approaches and better understand the molecular mechanisms underlying ferroptosis in atherosclerosis.